Effects of Additional Exercise Volume on Body Composition (Weight, Body Mass Index, and Fat Percentage) and Performance Metrics (Power, Strength, and Fatigue Index) in Adolescent Wrestlers - Kheirandish, Reza; Rahmani, Ahmad; Gorzi, Ali; Shaabani Ezdini, Ebrahim (Health Nexus, 2025)
This study investigated the effects of a structured two-week exercise intervention combining wrestling drills, resistance training, and high-intensity interval training (HIIT) on body composition and performance metrics in adolescent wrestlers aged 15-19 years. Twenty male wrestlers from Soltanieh city were divided into experimental and control groups. The experimental group underwent a structured exercise intervention including resistance training (once weekly at 50-55% 1RM), HIIT (four to five 35-meter sprints), and speed training (50-meter sprints), alongside regular wrestling drills. Body composition (weight, BMI, body fat percentage) and performance metrics (power, strength, fatigue index) were assessed pre- and post-intervention. Analysis of covariance revealed significant improvements in the experimental group for weight reduction (F(1,17)=8.24, p=0.007, η²=0.182), body fat percentage (F(1,17)=15.63, p<0.001, η²=0.297), power output (F(1,17)=12.81, p=0.001, η²=0.257), strength (F(1,17)=9.45, p=0.004, η²=0.203), and fatigue resistance (F(1,17)=8.32, p=0.006, η²=0.183). BMI changes remained non-significant between groups (F(1,17)=2.87, p=0.098, η²=0.072). The structured exercise intervention effectively improved body composition while maintaining or enhancing performance metrics in adolescent wrestlers. The significant improvements in power output, strength, and fatigue resistance, concurrent with weight reduction, suggest this approach as a viable alternative to traditional rapid weight loss methods. These findings provide valuable insights for developing evidence-based weight management protocols that prioritize both performance and athlete health.